ANALISIS PENGARUH LOGISTICS PERFORMANCE INDEX, EASE OF DOING BUSINESS DAN BUSINESS CONFIDENCE TERHADAP GLOBAL COMPETITIVENESS - Vidiya Hera Puspitasari; Evi Yulia Purwanti (Jurnal Ekonomi-Qu, 2021)
Competition can maximize capabilities and strategies to increase competitiveness, making countries aware of a country’s competitiveness. Many countries carry out economic cooperation to improve the country’s economy and competitiveness, one of which is Asean and its trading partners, the Regional Comprehensive Economy Partnership (RCEP). Trade is closely related to the logistics system and business economy. Logistics performance and business investment are considered to contribute to the competitiveness and economy of the country. This study aims to analyze the effect o logistics performance index (LPI), ease of doing business, and business confidence on global competitiveness. The object of research is Indonesia and RCEP member countries in 2013-2017. The type of data is secondary data in the form of panel data. The method of analysis is panel data regression analysis with the selected model using the fixed effect model (FEM). The result showed that the ease of doing business had a significant positive effect on global competitiveness, while the logistics performance index (LPI) and business confidence showed insignificant result on global competitiveness.